Species composition and bioecology of pests found in walnut plants - Xolmatova Saidaxon Qurbonboy qizi (Zien Journals, 2022)
Walnut is one of the most valuable fruits that nature gave us. It is widely used in various areas of our life. The walnut tree grows in almost every garden and its medicinal properties have already been written about in previous articles on this site. Every year bring us joy bountiful harvest walnuts are still facing problems. This article covers the diseases that affect the precious tree.
Keywords: Peanut; Bordeaux liquid; American white butterfly; Streptomyces avermitilis